Answer:
The equation is,
[tex]y = - \frac{4}{3}x - \frac{2}{3} [/tex]
Step-by-step explanation:
When a line is parallel to the other line, they will have the same gradient :
[tex]12x + 9y = 3[/tex]
[tex]9y = - 12x + 3[/tex]
[tex]y = - \frac{12}{9} x + \frac{3}{9} [/tex]
[tex]y = - \frac{4}{3} x + \frac{1}{3} [/tex]
We have already found the gradient. Next, we have to substitute the gradient and coordinates into the slope-form equation, y = mx + b :
[tex]y = mx + b[/tex]
Let m = -4/3,
Let x = -5,
Let y = 6,
[tex]6 = - \frac{ 4}{3} ( - 5) + b[/tex]
[tex]6 = \frac{20}{3} + b[/tex]
[tex]b = 6 - \frac{20}{3} [/tex]
[tex]b = - \frac{2}{3} [/tex]